2008
DOI: 10.1192/bjp.bp.106.034223
|View full text |Cite
|
Sign up to set email alerts
|

Non-traditional lifestyles and prevalence of mental disorders in adolescents in Goa, India

Abstract: The current prevalence of mental disorders in adolescents in our study was very low compared with studies in other countries. Strong family support was a critical factor associated with low prevalence of mental disorders, while factors indicative of adoption of a non-traditional lifestyle were associated with an increased prevalence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
99
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 126 publications
(110 citation statements)
references
References 33 publications
(29 reference statements)
9
99
2
Order By: Relevance
“…The mean scores observed in the current study may appear disproportionately higher than prevalence rates previously reported by previous studies of both Indian adolescents (7,12) as well as North American or Australian adolescents (44,45). However, it is important to distinguish such studies on the basis that these previous studies reported the prevalence of adolescents meeting the full diagnostic criteria for depressive disorders, such as Major…”
Section: Differences In Levels Of Symptomscontrasting
confidence: 54%
See 3 more Smart Citations
“…The mean scores observed in the current study may appear disproportionately higher than prevalence rates previously reported by previous studies of both Indian adolescents (7,12) as well as North American or Australian adolescents (44,45). However, it is important to distinguish such studies on the basis that these previous studies reported the prevalence of adolescents meeting the full diagnostic criteria for depressive disorders, such as Major…”
Section: Differences In Levels Of Symptomscontrasting
confidence: 54%
“…Pillai et al noted that previous research of mental disorders in adolescents in India reported a wide range of prevalence rates from 3% to 36% (7). Community-based studies of Indian adults have found prevalence rates of 61% for depressive symptoms and 16-34% for clinical depression (12).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Adolescence is a stage before entrancing in to adulthood. There may be many challenges in this period and it demands adjustment of many fronds [3][4][5][6][7] . Adolescence is commonly divided in to three periods.…”
Section: Introductionmentioning
confidence: 99%